2014
DOI: 10.5551/jat.18952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2C19 Polymorphism on Platelet Function Tests and Coagulation and Inflammatory Biomarkers in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Aim:Carriers of the reduced-function CYP2C19 allele receiving dual antiplatelet therapy (DAPT) with aspirin and clopidogrel exhibit diminished platelet inhibition and an increased risk of events. The purpose of this study was to investigate the effects of CYP2C19 gene variants on platelet function tests and coagulation and inflammatory biomarkers in patients undergoing elective percutaneous coronary intervention (PCI). Methods: This prospective, observational, multicenter study enrolled 104 consecutive Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…These results can be explained by the high local concentrations of eptifibatide achieved in IC administration in comparison to the IV route. Similar to abciximab and tirofiban, eptifibatide is a GPI that blocks the final common pathway of platelet aggregation by binding to platelet GP b/ a receptors, which bind to fibrinogen and other adhesive proteins that crosslink adjacent platelets 4,[33][34][35] . It also has dose-dependent antiplatelet, dethrombotic, and anti-inflammatory features [6][7][8][34][35][36] .…”
Section: Fig 2 Post-pci Timi Flow Gradementioning
confidence: 99%
“…These results can be explained by the high local concentrations of eptifibatide achieved in IC administration in comparison to the IV route. Similar to abciximab and tirofiban, eptifibatide is a GPI that blocks the final common pathway of platelet aggregation by binding to platelet GP b/ a receptors, which bind to fibrinogen and other adhesive proteins that crosslink adjacent platelets 4,[33][34][35] . It also has dose-dependent antiplatelet, dethrombotic, and anti-inflammatory features [6][7][8][34][35][36] .…”
Section: Fig 2 Post-pci Timi Flow Gradementioning
confidence: 99%
“…In the present study, the frequency of the carriers of at least 1 CYP2C19 reducedfunction allele was almost similar to that reported earlier by our group in different population samples. 14, 15 We could not find CYP2C19 gain-of-function alleles (*17) in the present study, so clinical studies that include large numbers of subjects are needed to determine the true frequency of CYP2C19 gain-of-function alleles (*17) in Japanese AMI patients.…”
Section: Discussionmentioning
confidence: 61%
“…14 We also reported that the platelet function tests, but not coagulation, inflammatory or cardiac biomarkers, seem to be useful for identifying carriers of CYP2C19 reducedfunction gene variants and for monitoring the efficacy of DAPT in patients undergoing elective PCI. 15 However, it is unclear whether CYP2C19 genotype-tailored antiplatelet therapy with adjunctive cilostazol is effective in inhibiting platelet aggregation in AMI patients with CYP2C19 reduced-function alleles. We conducted the present CALDERA-GENE (Controlled Anti-pLatelet meDical thErapy based on RApid CYP2C19 GENe Evaluation in acute myocardial infarction; UMIN000008151) study, an open-label, prospective multicenter study that enrolled Japanese AMI patients who underwent primary PCI.…”
Section: Measurement Of Biomarkers Of Blood Coagulation Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…В 2014 г. Nikolopoulos с соавт. опубликовали результаты мета-анализа 53 работ и продемонстрировали, что на-личие полиморфизма в гене PAI-1 приводит к повы-шению его активности в плазме, тем самым повышая риск развития ИМ [26]. Необходимо отметить, что уро-вень PAI-1 ассоциируется с высоким риском развития рестенозов и ТС после имплантации стентов с ле-карственным покрытием [27].…”
Section: Discussionunclassified